2009
DOI: 10.2466/pr0.105.f.1095-1102
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Taiwanese Children's Perceptions of Peace and Strategies to Make Peace: A Social and Cultural Perspective

Abstract: This exploratory study described Taiwanese children's perceptions of peace and what they think children can do to make peace. In-depth interviews were conducted with 60 Taiwanese children ages 4 to 18 years. The most predominant themes for the perceptions of peace were what peace is not, prosocial behaviors, positive emotions, and positive evaluations of peace. Approximately half of the children (48%) provided specific strategies for making peace. The suggested strategies generally were based on the child's im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Although parents included multiple themes of positive descriptions of peace in their answers to children, the most impressive notions of peace from parents in the minds of children were the negative descriptions of peace. Similar results were found in Deng and Shih's (2009) study on Taiwanese children's perceptions of peace and strategies to make peace in the same child sample. Based on Symbolic Interactionism, children develop an understanding of peace through social interactions of verbal and nonverbal actions and communications with their primary groups (LaRossa & Reitzes, 1993).…”
Section: Parent-child Communication About Peacesupporting
confidence: 86%
See 2 more Smart Citations
“…Although parents included multiple themes of positive descriptions of peace in their answers to children, the most impressive notions of peace from parents in the minds of children were the negative descriptions of peace. Similar results were found in Deng and Shih's (2009) study on Taiwanese children's perceptions of peace and strategies to make peace in the same child sample. Based on Symbolic Interactionism, children develop an understanding of peace through social interactions of verbal and nonverbal actions and communications with their primary groups (LaRossa & Reitzes, 1993).…”
Section: Parent-child Communication About Peacesupporting
confidence: 86%
“…As a result, we can concluded temporarily that peace education in the minds of Taiwanese children involves more of what not to do than what to do or what can be done. Deng and Shih (2009) reported that 52% of Taiwanese children, in contrast to 46% of children in Belgrade and only 9% of U.S. children (Walker, 2002), said that children could not do anything to make peace. More research is needed to investigate if this sense of vulnerability and powerlessness is related to parenting strategies for peace, culture, or other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation